Engineering methods for precipitation under a changing climate - Olsen, J. Rolf; Adamec, Kelcy Takahashi (American Society of Civil Engineers, 2020)
"This collection contains seven peer-reviewed papers on engineering design for precipitation extremes presented at the ASCE Workshop on Engineering Methods for Precipitation under a Changing Climate, held in Reston, Virginia, May 30, 2017"-- Provided by publisher
"Sponsored by Subcommittee on Hydroclimatology and Engineering Adaptation (HYDEA) of the Committee on Adaptation to a Changing Climate of the American Society of Civil Engineers."
Keywords: Flood control -- Congresses.; Climatic changes -- Congresses.; elektronické knihy; electronic books